Anomalous extensive landfast sea ice in the vicinity of Inexpressible Island, Antarctica - Mengxi, Zhai; Tiancheng, Zhao; Fengming, Hui; Xiao, Cheng; Aobo, Liu; Jiawei, Yuan; Yining, Yu; Yifan, Ding (Polar Research Institute of China - PRIC, 2019)
On 10 December 2017, a Chinese research vessel R/V Xuelong encountered an extensive area of landfast ice offshore Inexpressible Island (Antarctica) near the location where the fifth Chinese Antarctic research station is to be built. Using multi-source satellite images and weather data, we analyzed the ice conditions during the event season and reconstructed the development of landfast ice. Two stages in late September and early October were identified as contributing to the final ice extent. These two events are highly related to local- and large-scale weather conditions. Satellite images from 2003 to 2017 showed that four in fifteen years experienced severe landfast ice conditions, suggesting that it is not a rare phenomenon.